Photosynthesis, yield and raw material quality of sugarcane injured by multiple pests - Rossato, José A.S.; Madaleno, Leonardo L.; Mutton, Márcia J.R. [UNESP]; Higley, Leon G.; Fernandes, Odair A. [UNESP] (PeerJ, 2019)
Understanding sugarcane (Saccharum spp.) response to multiple pest injury, sugarcane borer (Diatraea saccharalis) and spittlebug (Mahanarva fimbriolata), is essential to make better management decisions. Moreover, the consequences of both pests on the sugarcane raw material quality have not yet been studied. A field experiment was performed in São Paulo State, Brazil, where sugarcane plants were exposed to pests individually or in combination. Plots consisted of a 2-m long row of caged sugarcane plants. Photosynthesis was measured once every 3 months (seasonal measurement). Yield and sugar production were assessed. The measured photosynthesis rate was negatively affected by both borer and spittlebug infestations. Photosynthesis reduction was similar on plants infested by both pests as well as by spittlebug individual infestation. Plants under spittlebug infestation resulted in yield losses and represented 17.6% (individual infestation) and 15.5% (multiple infestations). The sucrose content and the sucrose yield per area were reduced when plants were infested by multiple pests or spittlebug.
Keywords: Combined infestation; Diatraea saccharalis; Mahanarva fimbriolata; Plant-insect interactions; Sucrose